PEMBERIAN REWARD DALAM MENINGKATKAN MOTIVASI BELAJAR - Maulidina Sazidah; Refanti Madani Hanifah; Risa Vaniar Haliza; Arita Marini (Bajang Institute, 2023)
This research report aims to determine whether there is an influence on student learning motivation if given a reward. This research was carried out because of the low interest of students in learning in class, thus affecting exam results. The population in this study were all students of class V to be observed (observation). The method used in this study is a qualitative method, in which the method is used to examine the conditions of natural objects, (as opposed to experiments) where the researcher is the key instrument, data collection techniques are carried out by triangulation (combined), data analysis is inductive For other additions this study uses the library study method to be discussed in theory